1999
DOI: 10.1177/0021955x9903500404
|View full text |Cite
|
Sign up to set email alerts
|

HFC-365mfc: A Versatile Blowing Agent for Rigid Polyurethane Foams

Abstract: HFC-365mfc and HFC-245fa are now well documented as promising blowing agents, and their production will come on stream in a few years. However, none has the same ideal boiling point as CFC-11 or HCFC-141b. Blends may offer the best compromise to customize the different end-use requirements. Two different directions for further developments have emerged from our work: Two binary, non-azeotropic blends of HFC-365mfc with HFC-245fa or HFC-134a open the door to non-flammable blowing agents with a convenient boili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…The thermal conductivity of HFC-365mfc gas is 10.6mW•m -1 •K -1 at 25°C (2) . For cyclopentane many different values are given in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The thermal conductivity of HFC-365mfc gas is 10.6mW•m -1 •K -1 at 25°C (2) . For cyclopentane many different values are given in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the effective diffusion coefficient of HFC-365mfc in a PUR foam was found to be 1.0•10 -13 m 2 •s -1 . In the literature the values 3.1•10 -13 and 0.5•10 -13 m 2 •s -1 are given (13,1) . In an earlier study we have determined D eff to be 0.6•10 -13 m 2 •s -1 for cyclopentane (11) .…”
Section: Discussionmentioning
confidence: 99%
“…This result is likely due to the lower surface tension of the mixed polyol solution with a PFA content of 1.0 php, which allowed the mixed polyol solution to be more uniform and led to a higher nucleation rate. 1,17 The low surface tension of PFA itself (13.9 mN/m) may contribute to the decrease in surface tension of mixed polyol solutions with PFA contents. For the PFA content of 2.0 php, however, the cell size increased up to 181 μm.…”
Section: Morphology Of the Pu Foamsmentioning
confidence: 99%
“…Hydrofluorocarbon (HFC), a third-generation blowing agent, has also been used to prepare rigid PU foams. 1,7,16,17 Although PU foams prepared with HFC have the advantage of low ozone depletion potential (ODP), they are also known to have high global warming potential (GWP). As a result, a formulation with a new blowing agent for the preparation of rigid PU foam is needed, as the use of HFC is restricted by various environmental regulations, including the Montreal Protocol of 2016.…”
Section: Introductionmentioning
confidence: 99%
“…SOLVAY is committed to supplying a liquid zero ODP blowing agents for plastic foams as substitutes for the currently used HCFC-141b. Since 1995 we have published a series of papers on the development of HFC-365mfc as a substitute for HCFC-141b (1)(2)(3)(4)(5)(6)(7). HFC-365mfc has a boiling point of 40 C and a vapor thermal conductivity of 10.6 mW/m K, as shown in Table 1.…”
Section: Overviewmentioning
confidence: 99%